Cholesterosis Bulbi in a Painful Blind Eye with High Intraocular Pressure and Long Standing Total Retinal Detachment - Samina Jahangir Samina Jahangir, Haroon Tayyab, Ali Haider, Tehmina Jahangir, Sana Jahangir (Pakistan Journal of Ophthalmology, 2018)
This is case report of a 19 year old male who presented to the Ophthalmology Department of Jinnah Hospital Lahore in July 2011 with a painful blind left eye for the last two years. Examination of left eye showed no perception of light, circumcorneal injection, band keratopathy, pseudohypopyon of polychromatic crystals, polychromatic crystals embedded in iris stroma and aphakia. Intraocular pressure was 32 millimeters of Mercury. B scan ultrasound showed old retinal detachment. Right eye examination was normal. There were no associated systemic examination findings. He had a history of cataract surgery for left congenital cataract at the age of four years followed by sudden painless loss of vision three years after cataract surgery. In our eye department, he was started on topical cycloplegics, corticosteroids and topical and systemic anti-glaucoma medication and was made symptomatically comfortable. Retinal surgery was not contemplated taking into consideration his chronic retinal detachment and poor visual status.